Acute Respiratory Distress Syndrome - Arief Bakhtiar; Rena Arusita Maranatha (Jurnal Respirasi, 2018)
Acute respiratory distress syndrome (ARDS) is a syndrome, a combination of clinical and physiological observations that describe a pathological state. The pathogenesis of ARDS is not completely clear and there is no gold standard for diagnosis. ARDS is characterized by non-cardiogenic pulmonary edema, inflammation of the lungs, hypoxemia, and decreased lung compliance. Acute is defined as a symptom that occurs within one week of a known risk factor. Early clinical manifestations are shortness of breath (dyspneu and tachypneu) which then quickly develop into respiratory failure. ARDS was first described in 1967 by Asbaugh, et al., then the AECC made a definition that was finally refined by Berlin's criteria. Berlin's criteria divided the degree of hypoxemia into 3, namely mild, moderate, and severe, based on the arterial PO2 / FiO2 ratio and the need for PEEP (5 cm H2O or more) which can be given via endotracheal tube or non-invasive ventilation. Sepsis, aspiration of fluid or gastric contents, and multipe transfusion (>15 units/24 hours) are associated with a high risk of ARDS. Cases of ARDS related to pulmonary sepsis, such as pneumonia, inhalational trauma, and pulmonary contusions are as much as 46% or non-pulmonary sepsis as much as 33%. ARDS management includes oxygen therapy and supportive therapy, such as hemodynamics, pharmacotherapy, and nutrition. Further studies are still needed to get a good outcome for ARDS patients.